2020
DOI: 10.1016/j.heliyon.2020.e04565
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of dual solutions for an enhanced cross liquid flow past a moving wedge under the significant impacts of activation energy and chemical reaction

Abstract: The mathematical modeling and numerical simulation are conferred to offer the novel perception of binary chemical reaction with an activation energy aspect on magneto flow comprising Cross liquid inspired by a moving wedge. The influences of Soret and Dufour are also presented. The similarity procedure is utilized to modify the leading PDEs into a non-linear system of ODEs and then analyzed through a significant technique namely bvp4c based on the collocation method. The impacts of varying distinct parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The nonlinear ODEs ( 11) and ( 12), as well as the boundary condition (13), are numerically solved using the built-in solver of bvp5c MATLAB. The calculations have been performed for a variety of parameter values.…”
Section: Methods Of Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nonlinear ODEs ( 11) and ( 12), as well as the boundary condition (13), are numerically solved using the built-in solver of bvp5c MATLAB. The calculations have been performed for a variety of parameter values.…”
Section: Methods Of Solutionmentioning
confidence: 99%
“…Ramesh and Jyothi 12 used analytical and asymptotic approaches to investigate the two‐dimensional (2D) boundary‐layer flow and heat transfer over a wedge. Khan et al 13 demonstrated the dual solutions for traveling past a moving wedge where the activation energy and chemical reaction have a major effect. Singh et al 14 investigated the slip flow of a micropolar fluid through a permeable wedge due to several impacts by using an analytical method.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these achievable equations in the dimensionless form along with the associated boundary stipulations (10) have been resolved numerically using the colocation formula such as the bvp4c. This code is built-in software in MATLAB that gives the solution exercising the well-known 3-stage Lobatto IIIA formula [7,24,33] which is also based on the finite difference scheme. For the working process of the bvp4c package, first, introduce the new variables and with the help of them, we can receive the set of firstorder equations from the leading dimensionless equations.…”
Section: Single Solution Through Bvp4c Techniquementioning
confidence: 99%
“…Afterward, the works on the F-S flow were carried out by various researchers with different aspects as described in Refs. [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Dhlamini et al (2019) proved that the activation energy parameter boosts the concentration of chemical species in the boundary layer. A plethora of studies on chemical reactions and activation energy rates have been conducted until now, for instance, Khan et al (2020cKhan et al ( , 2019, Lu et al (2017), andShafique et al (2016).…”
Section: Introductionmentioning
confidence: 99%